Determination of the Senior High School Department Using the Expectation Maximization Algorithm - Yudiyana, I Made Gede; Sumichan, Andrew; Ridwan Satri0, Muhammad; Ibi Weking, Antonius (International Journal of Engineering and Emerging Technology; Vol 4 No 1 (2019): January - June, 2019)
High school is an educational institution that has directed students to concentrate or learn more in the field of science in accordance with the academic abilities of the students concerned. Generally the top high school has 3 department intended for students when climbing levels from grade 1 to grade 2, namely majors in Science, Social Sciences and Language. Nowadays with a growing human population, the number of students enrolled in a school is quite large, with the number generally in public schools 30 to 40 students per class. With the large number of students this will provide difficulties to determine the direction of each student if done manually. With this problem the researcher implements an EM (Expectation Maximization) method, this method is chosen because of its ability to get the highest probability value and can find the optimal parameters even though the available available map is incomplete or lacking. Using this method will make it easier for a school institution to determine the right direction for students